STUDY OF THE STATE AND PROBLEMS OF BUSINESS DEVELOPMENT IN THE UKRAINIAN ECONOMY DURING THE WAR (INNOVATIVE ECONOMY, 2024)
Nipialidi O.Yu., Kvasovskyi O.R. STUDY OF THE STATE AND PROBLEMS OF BUSINESS DEVELOPMENT IN THE UKRAINIAN ECONOMY DURING THE WARPurpose. The purpose of the article is to assess the current state of domestic business in the conditions of full-scale Russian armed aggression against Ukraine, to identify the main problems and difficulties faced by business entities during the war, as well as to outline guidelines for solving these problems in order to promote the sustainable development of national entrepreneurship.Methodology of research. The following general scientific methods of scientific research were applied in the process of research, as observation, comparison, generalization, etc. The methods of critical analysis of research results presented in the publications of scientists and expert practitioners, reviews of the latest news, systematization, typology, and analytical processing of statistical data of various international and national institutions were used to select and present the most visible indicators that verify the conclusions made through verbal and discursive considerations.Findings. Based on the analysis of statistical data, it was established that the economic situation in the country is extremely difficult and even critical. It was established that the management of Ukrainian enterprises does not have sufficient training and skills in the field of business management in such difficult operating conditions. It was proven that in risky and dangerous situations, managers cannot act according to old dogmatic rules, but are forced to use increased creativity and ingenuity.It was determined that for a thorough study of the current state of business in Ukraine, there is a critical lack of a statistical database on the development of entrepreneurship under martial law, and most importantly, no effective management models of business entities were developed in an environment of increased volatility of the business environment and variable determinants of its impact. The current state and needs of Ukrainian business were identified in order to develop a set of anti-crisis recommendations aimed at its stabilization and renovation in wartime conditions.Originality. Based on a thorough analysis, the article summarizes, systematizes, and specifies existing problems and obstacles for the functioning of domestic business in conditions of full-scale armed aggression. On the basis of this, a set of interrelated measures was developed, the implementation of which will contribute to the improvement of the business environment and the development of entrepreneurship in Ukraine. It is substantiated that the effectiveness of the practical implementation of the mentioned recommendations will depend on the joint efforts of entrepreneurs, the state, the public and international partners.Practical value. The provided relevant information about the peculiarities of starting and running a business in the conditions of modern challenges and threats and its effective management in crisis situations arising as a result of war can be used by interested domestic state institutions and organizations that implement the policy of stimulating the development of entrepreneurial activity, as well as business entities.Key words: business, entrepreneurship, war, martial law, subjects of entrepreneurial activity, relocation, business problems, support of entrepreneurial activity.
Keywords: business; entrepreneurship; war; martial law; subjects of entrepreneurial activity; relocation; business problems; support of entrepreneurial activity.